Zakat performance index / Abd Halim Mohd Noor, Rozman Md Yusof and Muhamad Rahimi Osman - Mohd Noor, Abd Halim; Md Yusof, Rozman; Osman, Muhamad Rahimi (Research Management Institute (RMI), 2012)
The raison d'etre of any organizations is their ability to fulfill its organizational objective. Similarly, zakat organizations being one of the Islamic institutions entrusted to address the economic imbalances among the muslim ummah have a daunting task. Data on zakat collection in several countries suggest that despite its increase, it is yet to reach its potential (Mahmood Zuhdi et al, 2006). This scenario is further compounded by the perceived inability of various zakat organizations to timely disburse their zakat fund. This chapter will introduce the problem statement, research questions, research objectives, significance and limitations of the study. Performance of zakat institutions in Malaysia varies according to states. Comparative studies on zakat collection, distributions and its effectiveness are yet to be undertaken. In Malaysia, with Islamic matters under the jurisdiction of the States rather than the Federal, zakat are collected and distributed by state-owned organizations. Despite being administered by state bodies and zakat payers are legally bound to fulfill their obligations, payments and distributions of zakat has yet to reach its full potential. Penalty for non-compliance of zakat, although in existence, were not enforced. The aforementioned scenario portrayed fulfilling zakat obligations as voluntary when it is in fact mandatory. The differences in state's performance are mainly attributed due to the differences in the zakat institution performance, level of awareness of zakat responsibility plus the economic development stage of the state.